The possibility of clinical bonding between metal/ceramic brackets to zirconia: in vitro study - Hu, Yichun; Gao, Jiayang; Huang, Xinyue; Li, Yutong; Chen, Ziyi; Zhan, Desong; Sano, Hidehiko; Carvalho, Ricardo M.; Fu, Jiale (Frontiers in Bioengineering and Biotechnology, 2024)
The present study aimed to assess the bond strength and durability of six bonding agents concerning their application to metal or ceramic brackets and zirconia. Six resin cement bonding agents (XT, XTS, RSBU, RGBU, SBPM, and GMP) were chosen for this investigation. Specimens were either stored in distilled water at 37°C for 24 hours or subjected to 5,000 thermocycles before conducting a Shear Bond Strength (SBS) test. Statistical analysis of the SBS data was performed using three-way ANOVA and Games-Howell tests (α = 0.05). The Adhesive Remnant Index was examined, and the debonding surface details on brackets and zirconia were observed. For metal brackets, all groups demonstrated clinically acceptable bond strength, irrespective of storage conditions, except for the XT group. Regarding ceramic brackets, all groups displayed acceptable bond strength after 24 hours of water storage. However, following thermocycling, a significant decrease in SBS was noted across all groups (p<0.05), with SBPM exhibiting a higher bond strength. Three-way ANOVA analysis indicated that SBS values were notably influenced by each factor, and an interaction among the three independent variables was observed (p=0.000). The reliable bond strength between ceramic brackets and zirconia was significantly lower after thermocycling compared to that of metal brackets and zirconia. SBPM exhibited consistent and robust bond strength between ceramic/metal brackets and zirconia across various storage conditions. Furthermore, the HEMA-free adhesive demonstrated a potentially more consistent bonding performance compared to the HEMA-containing adhesive employed in this study.